A slice‐wise latent structure regression method for the analysis of functional magnetic resonance imaging data. (10th August 2013) - Fayyaz, Ahmad; Chaudhary, Safee Ullah; Kim, Sung‐Ho; Park, Hyunwook
ABSTRACT: We introduce a novel slice‐wise latent structure regression (LSR) method for the analysis of functional magnetic resonance imaging (fMRI) data instead of the conventional voxel‐wise generalized least squares (GLS) method. LSR method is designed for application to data sets from slices where fMRI responses (voxelsY * of a slice) are highly correlated with the design matrixX * . Also, we compared the performances of LSR, principal component regression (PCR), and GLS methods in terms of model parameters using experimental fMRI data. The LSR method exhibits an enhanced predictive ability and model coefficients as compared to the PCR and GLS methods. © 2013 Wiley Periodicals, Inc. Concepts Magn Reson Part A 42A: 130‐139, 2013.